2001
DOI: 10.1023/a:1009801706928
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: CAP algorithm allowed continuous overdrive atrial pacing without major side effects. Triggers of paroxysmal atrial fibrillation induction, such as premature atrial complexes, were critically decreased. Paroxysmal atrial fibrillation episodes were reduced in patients with atrial pacing percentage lower than 90 % during DDDR pacing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…While pacing of atria under anesthesia is considered a standard technique when examining propensity toward AF in both animal models and human patients (36,41), a study in free-running mice fitted with telemetric monitoring would be an interesting future study. Although not all the animals were inducible, our results indicated that untreated T1Dx animals had overall significantly greater frequency and longer duration of atrial tachy-arrhythmias, including AF, atrial tachycardia and brady-tachy syndrome (which has been reported to precede AF) (42). Specifically, the frequency and duration of AF episodes were greater in T1Dx animals vs. controls.…”
Section: Discussionmentioning
confidence: 56%
“…While pacing of atria under anesthesia is considered a standard technique when examining propensity toward AF in both animal models and human patients (36,41), a study in free-running mice fitted with telemetric monitoring would be an interesting future study. Although not all the animals were inducible, our results indicated that untreated T1Dx animals had overall significantly greater frequency and longer duration of atrial tachy-arrhythmias, including AF, atrial tachycardia and brady-tachy syndrome (which has been reported to precede AF) (42). Specifically, the frequency and duration of AF episodes were greater in T1Dx animals vs. controls.…”
Section: Discussionmentioning
confidence: 56%